Development and usability testing of an audit and feedback tool for anesthesiologists. Issue 1 (4th February 2019) - Barbeito, Atilio; Segall, Noa
Abstract: Background: We describe the creation and evaluation of a personal audit and feedback (A&F) tool for anesthesiologists. Methods: A survey aimed at capturing barriers for personal improvement efforts and feedback preferences was administered to attending anesthesiologists. The results informed the design and implementation of 4 dashboards that display information on individual practice characteristics as well as comparative performance on several quality metrics. The dashboards' usability was then tested using the human-centered design framework. Results: Anesthesiologists listed lack of information on current practice as the main barrier for improvement. Regarding usability, participants gave the dashboards an average score of 3.8 (scale 1–5) on consistency, learnability, and information organization, and performed the assigned tasks well, with an average score of 89% (range 79–100%). Conclusions: We describe the design, implementation, and usability testing of an innovative tool that utilizes data derived from the electronic health record (EHR) system to provide A&F to anesthesiology providers.